2022
DOI: 10.3389/fpls.2021.814658
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Water Consumption of Wheat Varieties Are Affected by Root Morphology Characteristics and Post-anthesis Root Senescence

Abstract: Selecting high-yielding wheat varieties for cultivation can effectively increase water use efficiency (WUE) in the Huang–Huai–Hai Plain, where is threatened by increasing water shortages. To further identify the difference in water use and its relationship with root morphology and senescence characteristics, wheat varieties with different yield potentials—Yannong 1212 (YN), Jimai 22 (JM), and Liangxing 99 (LX)—were studied in a high-yielding wheat field. The water consumption percentage (CP) in YN decreased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Since there is a paucity of studies on RWU in alpine meadows, this paper is based on the study of root growth characteristics and water consumption capacity of maize and other ( Yu et al., 2015 ; Zheng et al., 2022 ) crops as an analogy to alpine meadows. The results showed that the water consumption of plants differed in different phenological stages, with the maximum water consumption in the early stage of plant growth and decreasing in the maturity stage.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is a paucity of studies on RWU in alpine meadows, this paper is based on the study of root growth characteristics and water consumption capacity of maize and other ( Yu et al., 2015 ; Zheng et al., 2022 ) crops as an analogy to alpine meadows. The results showed that the water consumption of plants differed in different phenological stages, with the maximum water consumption in the early stage of plant growth and decreasing in the maturity stage.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the mechanism influencing RWU can be focused on the influencing factors that determine RWU capacity. Most studies have focused on root factors when exploring the influencing factors (Zheng et al, 2022), however, we believe that roots and soil are inseparable. Thus, the study of two key factors, RLD, and soil hydraulic conductivity, will improve the understanding of the mechanism that impacts RWU.…”
Section: Figurementioning
confidence: 99%
“…On the time scale, the RLD in alpine meadows was significantly greater in the re-greening stage than in the wilting stage, and the RLD in the wilting stage decreased by 16.2% on average compared to the re-greening stage. This phenomenon is related to the plant growth process, and there are some differences in the water consumption of plants in different phenological stages, with higher water consumption in the early stage of plant growth and a gradual decrease in the later stage of growth (Yu et al, 2015;Zheng et al, 2022). Roots are important organs for plant water uptake, and when plants consume more water, the corresponding root index tends to be larger.…”
Section: Characteristics and Distribution Functions Of Rld Distributi...mentioning
confidence: 99%
See 1 more Smart Citation